2009
DOI: 10.1021/jf9000605
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 23Na Magnetic Resonance Imaging of Model Foods

Abstract: Partial (23)Na MRI invisibility in muscle foods is often referred to as an inherent drawback of the MRI technique, impairing quantitative sodium analysis. Several model samples were designed to simulate muscle foods with a broad variation in protein, fat, moisture, and salt content. (23)Na spin-echo MRI and a recently developed (23)Na SPRITE MRI approach were compared for quantitative sodium imaging, demonstrating the possibility of accurate quantitative (23)Na MRI by the latter method. Good correlations with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Indeed, this effect has also been observed when salting of Atlantic salmon and cod fillet pieces were studied using 23 Na MRI where the MRI visibility factors ranged from 22 to 89% . However, when the common 23 Na spin‐echo MRI technique was compared with the recently developed 23 Na single‐point ramped imaging with T 1 enhancement (SPRITE) MRI technique for quantitative sodium imaging, it became clear that sodium MRI invisibility is a methodological problem that can easily be circumvented by using the SPRITE MRI technique. SPRITE is a ramped‐gradient version of the well‐known single point imaging (SPI) technique, and it has a number of advantages compared with SPI, being more time efficient, gentle for the equipment, and more tolerant to inhomogeneity of the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, this effect has also been observed when salting of Atlantic salmon and cod fillet pieces were studied using 23 Na MRI where the MRI visibility factors ranged from 22 to 89% . However, when the common 23 Na spin‐echo MRI technique was compared with the recently developed 23 Na single‐point ramped imaging with T 1 enhancement (SPRITE) MRI technique for quantitative sodium imaging, it became clear that sodium MRI invisibility is a methodological problem that can easily be circumvented by using the SPRITE MRI technique. SPRITE is a ramped‐gradient version of the well‐known single point imaging (SPI) technique, and it has a number of advantages compared with SPI, being more time efficient, gentle for the equipment, and more tolerant to inhomogeneity of the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…For muscle‐based foods, the technique would be, for example, useful for quantitative studies of salt distributions. In cases where only the total content of NaCl is of interest, the more rapid bulk relaxation measurements (FID or CPMG) will be adequate …”
Section: Introductionmentioning
confidence: 99%
“…However, the signal intensity data from spin-echo imaging sequence proved unsatisfactory for this purpose. Veliyulin et al (2009) have shown poor correlation between NaCl content determined by chemical method and the spin echo MRI data. However, the short component T 2a gave a very good correlation with salt content, with a linear regression of y = 5.43x (R 2 = 0.973) with salt concentration (%) as the independent variable and change in T 2a (%) as the dependent variable.…”
Section: Transverse Relaxation Time (T 2 )mentioning
confidence: 95%
“…Due to the additional quadrupolar interaction in the quadrupolar nuclei, it often resulted in fast spin-spin transverse relaxation and broad resonance, hindering high resolution imaging. Despite this, 23 Na MRI is still a good diagnostic technique for localizing and quantifying the sodium concentration in materials such as foods (21), soft tissues (22), bone cartilages (23), and cements (24). Most of today's 23 Na imaging is done on nonrigid samples, or highly mobile sodium ions, where the quadrupolar interaction is expected to be small.…”
Section: Al Images Of Inorganic Saltsmentioning
confidence: 99%